Selection of territorial habitat in a declining population of Lapland Longspurs (Calcarius lapponicus) - Fjeldheim, Vegard Bang; Byrkjedal, Ingvar; Lislevand, Terje (Ornis Norvegica, 2023)
Cover photo: Male Lapland Longspur in its breeding habitat. Photo: Vegard B. Fjeldheim. The population of Lapland Longspur Calcarius lapponicus has declined drastically in the Scandinavian mountains over the last decades. One hypothesis is that the population decline has been caused by a change in vegetation composition, specifically an increase in lichen cover leading to a possible decrease in seed-producing plants. We tested the hypothesis by recording vegetation composition inside and outside Lapland Longspur territories in a 10 km2 study area at Hardangervidda, southern Norway, where longspurs previously bred in high numbers. Vegetation composition was recorded by percentage coverage in 295 1 x 1 m quadrats laid out evenly over the study area and compared to a similar treatment of 85 points inside 17 territories of Lapland Longspurs. No difference in lichen coverage or coverage by seed-producing plants was found inside versus outside territories. Instead, Lapland Longspurs were found to establish their territories in the upper part of the study area, where the snow melts earlier. Also, the occupied territories had an orientation towards the sun (sector S–W). Precipitation has increased strongly in the western parts of the Scandinavian Peninsula in recent decades. Falling as snow in the mountains, the increased precipitation leads to delays in spring thaw which could reduce the availability of breeding habitat for Lapland Longspurs during territorial establishment. We suggest that changes in spring conditions could be responsible for the species’ population decline in the western parts of the Scandinavian Peninsula.